iReach: new multisensory technology for early intervention in infants with visual impairments - Gori, Monica; Petri, Stefania; Riberto, Martina; Setti, Walter (Frontiers in Psychology, 2025)
Visual impairments have profoundly adverse consequences for infants. They affect infants’ spatial and motor skills, playing, socializing and psychological well-being. Early therapeutic interventions to foster these abilities are needed to improve their quality of life. Effective rehabilitation technologies depend on a better understanding of the neuroscientific bases of multisensory and body processing. However, these abilities can only be assessed qualitatively based on observational approaches. Technological solutions are still unavailable due to the complexity of conveying a signal to visually impaired infants that they will assuredly understand. With iReach, we aim to address this problem. Specifically, we will design and develop a multisensory system that will provide non-invasive recording and training of the sensory-motor skills. It will be compatible with simultaneous behavioral and brain activity response measures. For the first time, with iReach we will train and directly quantify visually impaired infants’ sensory-motor abilities, offering a cost-efficient system for early intervention.